Pendidikan Agama Dan Moral (Dalam Tafsir Surat Al-Lukman Ayat 12-19) - Siswanto, Heru (Sekolah Tinggi Agama Islam Sabilul Muttaqin Mmojokerto, 2024)
This research aims to: 1) find out how religious and moral education was instilled by Luqman Al-Hakim. 2) know Luqman Al-Hakim's message contained in Q.S. Luqman verses 12 to 19. This research is a type of qualitative research using a library research or literature review approach, with primary data being the Koran Surah Luqman verses 12 to 19, and secondary data is the tafsir Al-Maroghi by Ahmad Mustofa Al-Maraghi, tafsir M . Quraisy Shihab by M. Quraisy Shihab and Tafsir Ibn Kathir by Imam Abi Al-Hasan Ali Bin Ahmad, books and scientific works, journals and various other sources, which are related to research. The results of this research show that there are four messages contained in Surah Luqman verses 12 to 19 in accordance with religious and moral education. These four messages are in accordance with the basics of religious and moral education, namely instilling aqidah in children, teaching them to be grateful and devoted to Allah and their parents, getting them used to doing good deeds from an early age, and teaching them noble morals and ethics in interacting with others. As exemplified by Rasulullah SAW. Keywords: Religious education; moral; Q.S Luqman verses 12 – 19